Prognostic Factors for Parasagital Meningiomas Recurrence - Perepelytsia , Vadym; Sirko , Andrii (The Ukrainian Scientific Medical Youth Journal, 2023)
the study is relevant due to high prevalence of this type of pathology. Meningiomas account for 18% to 34% of all primary brain tumors. Parasagital meningiomas occur in 24.3% to 38.6% of cases. Despite their predominantly benign nature, parasagital meningiomas are more likely to recur/continue growing than meningiomas in other areas (18% to 40%). The key purpose of the study was to analyze the prognostic factors of parasagital meningiomas recurrence/continued growth, which will eventually improve surgical treatment outcomes.  We conducted a retrospective and prospective analysis of 199 parasagital meningioma patients who were treated in Mechnikov Dnipropetrovsk Regional Clinical Hospital, Dnipropetrovsk Regional Council, from 2000 to 2021 inclusive. This article is based on a comparative analysis of the results of examination and surgical treatment and further analysis of pathohistological conclusion in two study groups. The first group included 180 (90.5%) patients with no recurrence/continued growth and second group included 19 (9.5%) patients with detected postoperative parasagital meningioma (PM) recurrence/continued growth. The selected patients were analyzed for demographic data (gender, age); computed tomography and magnetic resonance brain imaging results before and after adding an intravenous contrast (in terms of key characteristics); angiographic studies data (computed tomography angiography/selective digital subtraction cerebral angiography); surgical radicality; pathohistological conclusions; recurrence-free period duration (one to 20 years after the surgery). In the follow-up period, 19 (9.5%) patients had PM recurrence/continued growth. In the first year after the surgery, only 2 of those patients had continued PM growth; within 5 years (60 months), 12 patients; within 10 years, 17 patients; the percentage of no- recurrence patients, based on censored data (recurrence-free survival), was 99.0% (95% CI, 97,6-100), 93,1% (95% CI, 89.3-96.9). and 87.5% (95% CI, 81.6-93.4) in the above follow-up periods. The actual median time to recurrence in our study was 44.1 (25.7; 85.4) months. It means that the majority (12 of 19 patients; 63.2%) of continued PM growth was detected within 5 years after the surgery. The last case of PM recurrence was diagnosed after 13 years (154.5 months) of the follow-up. Thus, recurrence-free 5- and 10-year survival in PM patients is as follows: in case of total tumor removal (Simpson I), 96.0% and 85.5%, respectively; in case of non-radical removal (Simpson II-V), 88.9% (p<0.05) and 81.9% (p<0.05), respectively. At the same time, non-radical surgery in type I-II SSS invasion by the PM reduces 5- and 10-year recurrence-free survival to 86.6% (p<0.01) and 78.3% (p<0.01), respectively; in case of tumor size of up to 54 mm, the indicators are 95.5% and 91.4%; with tumor size >54 mm, they are as low as 87.5% (p<0.001) and 72.5% (p<0.001); in case of type I-III or V-VI SSS damage according to M. P. Sindou and J. E. Alvernia, 94.0% and 89.1%; and in case of type IV invasion, 66.5% (p<0.01) and 43.5% (p<0.001); in female patients, 95.2% and 88.5%; in male patients, 84.8% (p<0.05) and 73.0% (p<0.01). According to the Cox regression proportional hazards model, the relative risk of tumor recurrence/continued growth increases by: 7.04 times (95% CI, 2.33-21.2) in case of initial PM size >54 mm (p<0.001); 5.57 times (95% CI, 1.27-24.34) in case of non-radical (Simpson II-V) tumor removal during primary intervention (P<0.05); 10.1 times (95% CI, 1.31-78.1) in case of type I-II SSS invasion by the PM or incomplete (Simpson II-V) tumor removal (p<0.05); 3.25 times (95% CI, 1.32-8.02) in male patients (p<0.01); 3.33 times (95% CI, 1.10-10.12) in case of type IV SSS invasion (according to M.P. Sindou and J.E. Alvernia) (p<0.05). Adequate analysis of the results obtained will help the neurosurgeons plan the optimal surgery volume and ensure further postoperative recurrence-free period and improved long-term treatment outcomes.